QUALITATIVE RESEARCH: TYPES, ESSENCE AND ADVANTAGES - Josephine Oranga; Audrey Matere (RADJA PUBLIKA, 2023)
The main aim of qualitative research is to explore and provide deeper, comprehensive and detailed description of phenomena rather than quantifying data and testing hypotheses. Notably, qualitative research describes and explains relationships, individual experiences and group norms. The objective of this article is, thus, to explore and describe the essence, types and advantages of qualitative research through a systematic review of related literature. Accordingly, the types/designs under qualitative research are: narrative, grounded theory, phenomenology, case study and ethnography. Moreover, sampling methods under qualitative research are mainly, purposive, criterion, convenience and snowballing. On the other hand, data in qualitative studies are collected by use of interview guides/schedules, focus group discussions and observation (non-participant and participant). Consequently, the advantages of qualitative studies include: flexibility and spontaneity (allows for the adaptation of interview items as the research progresses and need arises), does not require a large study sample, offers the opportunity to meet the respondents, encourages discussion with the participants, allows for the collection and interpretation of non-verbal cues (smiles, frowns, tears) and offers the opportunity to seek clarification, probe further and gain deeper understanding. Notably, the direct involvement of the researcher provides him/her the opportunity to get relevant responses.